2020
DOI: 10.1016/j.rbmo.2020.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Infertility remains a top stressor despite the COVID-19 pandemic

Abstract: Research question: What is the psychological impact of the COVID-19 pandemic on infertility patients?Design: An anonymous cross-sectional online survey was sent to patients who attended a large university-affiliated infertility practice in the USA between 1 January 2019 and 1 April 2020. At three different time-points respondents were asked to note their top three stressors, from a list of 10 commonly reported life stressors. Results:The questionnaire was sent to 10,481 patients, with 3604 responses (response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 4 publications
6
57
0
6
Order By: Relevance
“…COVID-19 was the third most common stressor among the respondents in the early stages of the pandemic (first days of March); nevertheless, in the latest period (first days of June), COVID-19 was responsible for stress with an incidence similar to infertility (63% and 66%, respectively). In this study, only 6% of patients stated that infertility treatment (including IVF) should not be offered during the COVID-19 pandemic [23]. In agreement with this data, our study showed that the occurrence of anxiety and/ or depression was significantly associated with time spent on COVID-19 related news per day.…”
Section: Discussionsupporting
confidence: 87%
“…COVID-19 was the third most common stressor among the respondents in the early stages of the pandemic (first days of March); nevertheless, in the latest period (first days of June), COVID-19 was responsible for stress with an incidence similar to infertility (63% and 66%, respectively). In this study, only 6% of patients stated that infertility treatment (including IVF) should not be offered during the COVID-19 pandemic [23]. In agreement with this data, our study showed that the occurrence of anxiety and/ or depression was significantly associated with time spent on COVID-19 related news per day.…”
Section: Discussionsupporting
confidence: 87%
“…Research finds that response rates in this range may not be associated with response bias and that large response rates in smaller samples may pose greater concerns for generalizability [ 19 ]. Further, given the similarities in overall acceptance of and psychological distress associated with the recommendations between our study and the previously published work using US patient populations [ 7 , 12 ] and internationally [ 20 , 21 ] it appears likely that our study results may be generalizable. Finally, although it is possible that participants who were the most distressed could have been more likely to respond to our survey than less distressed participants, our results show that a large percentage of fertility patients experienced distress as a result of the cancellation or delay of fertility care due to COVID-19.…”
Section: Discussionsupporting
confidence: 60%
“…Although the COVID-19 pandemic was rapidly spreading, the death toll was rapidly escalating and news reports of overburdened medical facilities were abundant; some physicians and patients reported that they were shocked or distressed by the recommendation to temporarily pause treatment [ 6 , 7 ]. Given the limited amount of time between the release of the national and international recommendations related to delaying fertility care and contact with patients regarding the cancellation or delay of their treatment, it is unclear if patients fully understood and/or accepted the rationale for delaying fertility care.…”
Section: Introductionmentioning
confidence: 99%
“…Coronavirus was the third (53.6%) most common stressor in March but the second (63%) most common in April, almost as high-ranking as that of infertility itself. They concluded that despite the global pandemic, the stress of infertility remained a significant stressor, comparable to the pandemic itself [128].…”
Section: Perceptions Coping Emotions and Stress Levels In Infertilmentioning
confidence: 99%